Organic carbon burial and their implication on sea surface primary productivity in the middle Okinawa Trough over the past 200 ka - Jing, Yunge; Zhang, Taoliang; Zhu, Ben; Zhao, Jingtao; Zhao, Xiaoxiao; Dou, Yanguang; Li, Qing; Cai, Feng; Hu, Bangqi; Dong, Liang (Frontiers in Marine Science, 2024)
The long-term burial of organic carbon in marginal seas plays a critical role in Earth’s carbon cycle and climate change. However, the mechanism of organic carbon (OC) burial in the Okinawa Trough (OT) during glacial-interglacial timescales remains unclear. In this study, we analyzed the foraminiferal carbon isotopes, total organic carbon (TOC), and δ13C-TOC over the past 200 ka in core Z1 collected in the central OT. We aimed to reveal the history of OC burial in the middle Okinawa Trough during the past 200 ka, and we combined our findings with relevant paleoenvironmental indices to reveal underlying mechanisms. We found reduced surface primary productivity during MIS 6, which may indicate changes in the pathways of the Kuroshio Current (KC). Furthermore, we observed decoupling between high TOC flux and low OC burial during glacial periods. We proposed that the dilution effect caused by the high sedimentation rate and poor OC preservation during the glacial period resulted in the low TOC content. Ventilation of the North Pacific Intermediate Water (NPIW) regulated the redox conditions of the intermediate water in the Okinawa Trough. Additionally, the intensified Kuroshio Current during interglacial phases led to water column stratification, creating reducing conditions in the bottom water and facilitating improved OC preservation. Subsequently, the enhanced water column oxygenation resulting from the oxygen carried by the intensified glacial NPIW weakened the burial of OC. This study sheds new light on our understanding of the carbon cycle in marginal seas on a glacial-interglacial timescale.